Optimization of Regional Tax Revenues in West Nusa Tenggara Province in 2018-2022 - Yanti, Putri; Alwi, Muhammad; Agustiani, Eka (West Science Accounting and Finance, 2024)
This research aims to analyze the Optimization of Regional Tax Revenues in West Nusa Tenggara Province for 2018-2022. The research method used is quantitative descriptive analysis. The data processed is the West Nusa Tenggara Province Budget Realization Report for 2018 to 2022. The data analysis technique used in the research is to calculate the optimization, effectiveness and efficiency of NTB Province regional tax revenues for 2018-2022. The results of this research show that regional tax revenues from 2018-2022 are not yet optimal because the effectiveness of regional taxes is below 100% and above 100%, the realization of tax revenues from 2018-2022 has not exceeded the tax revenue target. Meanwhile, regional tax efficiency is <10%, namely 5% from 2018-2022. Regional tax revenues in West Nusa Tenggara Province from 2018-2022 are not yet optimal where the level of optimization. The implications of this research provide information that the optimization of regional tax revenues in NTB should be optimal, one of which is by looking at the effectiveness and efficiency of regional tax revenues as seen from the targets and realization of regional tax revenues.